Risalah Cinta dalam Pandangan Hadis - Rindi Ananda Zulfikar Erada; Raden Roro Sri Rejeki Waluya Jati; Dadang Darmawan (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about the treatise of love. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about love in the history of Bukhari no. 12. The results and discussion of this study indicate that the status of the hadith is authentic with the qualifications of maqbul ma'mulbih for the practice of Islam in strengthening faith through love for brothers and sisters. This study concludes that the hadith narrated by Bukhari no. 12 are relevant to be used as the basis of faith through love for brothers and sisters.